Identification of Babesia capreoli in an Ixodes nipponensis tick obtained from a Korean water deer - Ku, Ji-Yeong; Kim, WooChan; Yoon, Ji-Seon; Park, Jinho (Journal of Biomedical Translational Research, 2023)
Babesiosis is a tick-borne disease caused by intraerythrocytic protozoa. Despite the increasing acknowledgement that babesiosis represents a threat to animal and human health, to date there have been few studies focusing on the disease in the Republic of Korea (ROK). In the present study, we report a Babesia capreoli infection in an Ixodes nipponensis tick obtained from a Korean water deer (Hydropotes inermis argyropus). The tick was identified with polymerase chain reaction analysis as I. nipponensis (Japanese hard tick). A phylogenetic analysis based on the 18S rRNA gene sequences revealed that the isolate found in I. nipponensis belonged to the B. capreoli lineage and was distinct from the Asian, European, and North American lineages of Babesia divergens. Although our isolate belonged to the B. capreoli lineage it did not form a cluster with others isolates in the same lineage; this may be due to differences in the tick species that transmit B. capreoli or in the host species. We were unable to identify the reservoir host for our case of B. capreoli transmission, though regional ticks may be the primary vector. This study confirms the presence of B. capreoli in the ROK, and its presence suggests that further study is warranted to determine its prevalence and pathogenicity in wild and domesticated animals.